Effects of treated wastewater irrigation on soil salinity and sodicity in Sfax (Tunisia): A case study - Belaid, Nebil; Neel, Catherine; Kallel, Monem; Ayoub, Tarek; Ayadi,, Abdel; Baudu, Michel (Revue des sciences de l'eau / Journal of Water Science, 2010)
In arid regions such as near Sfax (Tunisia), treated wastewater effluents (TWE) are often applied as agricultural irrigation. Irrigation TWE usually contain large amounts of carbon, nitrogen and sodium. The objective of this study was to evaluate the impact of TWE irrigation on soil salinity and sodicity. In the city of Sfax, two sites were selected with two soil types (fluvisol and calcisol) having been irrigated for 4 and 15 years respectively. Soils were sampled at three different depths (0-30, 30-60 and 60-90 cm) in the TWE irrigated area and in a non-irrigated control area. Irrigated and non-irrigated study soils were analyzed for pH, nitrate and ammonia, electrical conductivity (ECs), exchangeable sodium percentage (ESP), sodium absorption ratio (SAR) and soil organic matter.The fluvisol, irrigated for only four years, is more affected by salinity than the calcisol irrigated for 15 years. In the upper fluvisol layer irrigated by the treated wastewater, ECs reach 8 mS•cm-1 and ESP a value of 15% while in all layers of the calcisol, ECs and ESP are lower and rarely exceed 4 mS•cm-1 and 6% respectively. This result is due to a combination of factors in the fluvisol treatment area including texture, cation exchange capacity, irrigation procedure and crop management.